Wondering PTCA Wire: Retrieval by Tangling Technique - Sinha, Santosh Kumar (Cardiol Res, 2015)
A 38-year-old man underwent coronary angiography in our institution due to acute myocardial infarction as part of pharmaco-invasive strategy following thrombolysis. The patient showed total occlusion of mid left anterior descending (LAD) artery which was tortuous and calcified. The planned treatment was percutaneous coronary intervention (PCI) of culprit artery with wire being “jailed” in obtuse marginal branch of left circumflex artery (LCX) as left main was short and because of lesion characteristics. After successful stent implantation in the LAD, the “jailed” wire fractured as guiding catheter got deeply intubated as stent was being deployed in LAD. Initially, two balance middle weight (BMW) wires were used to retrieve but failed. Wire was wondering as it moved to proximal LCX, left main, partly into aortic sinus, sometimes proximal LAD and finally to LCX again during retrieval. Then it was decided to use tangling technique with the help of three BMW wires acting as rescue wires. The proximal ends of all three wires were inserted together in a torque device which were firmly screwed and rotated 40 - 50 times in circular pattern. During this rotational motion, the broken segment was tangled within these rescue wires and all four wires were removed together.